RELATIONSHIP BETWEEN ETHNORELIGIOUS CONFLICT TRAUMA IN 1999-2004 WITH THE LEARNING MOTIVATION OFSTUDENTS FROM NORTH HALMAHERA - Blandina, Olivia Asih (LPPM Universitas Hein Namotemo, 2018)
The conflict in North Halmahera affects various aspects of community life there. This study aims to determine the relationship between ethnoreligious conflict trauma in 1999-2004 with the motivation to study the students of North Halmahera. The sample of this research is students from North Halmahera who are studying at Satya Wacana Christian University. Samples taken as many as 39 people based on purposive sampling technique. The data were collected using two scales: trauma scale and learning motivation scale. The result of linearity test (F statistic test) showing F value equal to 3,494 with significance level 0,046 (p <0,05). The result of the correlation coefficient is - 0.409 (p <0.05) The value - 0.409 indicates a negative direction, which means that the relationship is opposite, ie when the trauma is high then the learning motivation is low, whereas the trauma is low then the learning motivation is high Interpretation of the value r is strong enough because it is in the range of 0.401 - 0.600.The probabilitation value of this result is 0.010 (p <0.05) so that the correlation relationship is declared significant.From this result obtained the results that the correlation coefficient value indicates there is a significant negative relationship strong enough between trauma ethnoreligus conflict in 1999-2004 with the motivation to study the students of North Halmahera.